Multiscale Modeling of Myocardial Electrical Activity: From Cell to Organ - Trenor, Beatriz; Romero, Lucia; Cardona, Karen; Gomis, Julio; Saiz, Javier; (Jr.), Jose Maria Ferrero (IntechOpen, 2011)
None